The effectiveness of problem-based learning in gynecology and obstetrics education in China: A meta-analysis of randomized controlled trials. Issue 9 (5th March 2021) - Bi, Siwei; Liu, Ruiqi; Li, Jingyi; Gu, Jun
Abstract: Background: A meta-analysis was conducted to assess the effectiveness of problem-based learning (PBL) in gynecology and obstetrics education in China. Methods: English and Chinese databases were systematically searched for eligible studies that compared the effects of PBL and traditional teaching methods measuring theoretical knowledge, student satisfaction, clinical operations, and clinical practice scores in gynecology and obstetrics education in China. The authors restricted included studies to randomized controlled trials and performed a meta-analysis. Standardized mean difference (SMD) and risk ratio with 95% confidence interval (CI) were estimated Results: A total of 38 randomized controlled trials with 3005 participants were included. Compared with traditional teaching group, the PBL group significantly increased theoretical knowledge scores (SMD: 3.17, 95% CI: 2.28, 4.07), student satisfaction (risk ratio: 1.29, 95% CI: 1.16, 1.43), clinical operations (SMD: 1.15, 95% CI: 0.93, 1.37) and clinical practice (SMD: 2.17, 95% CI: 3.63, 2.71). Conclusion: The current research shows that PBL in gynecology and obstetrics education in China is more effective than the traditional teaching in enhancing theoretical knowledge, student satisfaction, clinical operations, and clinical practice scores. However, more delicate-designed studies on this topic are needed in the future to validate these results. Abstract : Supplemental Digital Content is available in the text